1999
DOI: 10.1002/(sici)1521-4109(199905)11:5<362::aid-elan362>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chlorite in Drinking Water Using Capillary Electrophoresis with Amperometric Detection

Abstract: Capillary electrophoresis with end-column electrochemical detection (CEEC) was used to determine chlorite (ClO 2 À ) in drinking water. Two CE methods were developed. The ®rst method used a positive CE polarity with a 25 mM Borate buffer, pH 8.9. The second method used a negative CE polarity and a 25 mM phosphate buffer, pH 7.5 with 1 mM dodecyl trimethyl ammonium bromide (DTAB) added to reverse the EOF. The required detection potential was 1.0 V (vs. Ag/AgCl) in the positive polarity mode and 0.90 V (vs. Ag/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The interaction of the separation voltage with a working electrode placed in an in‐channel configuration leads to a negative half‐wave potential shift under reverse polarity conditions using a single channel method . In the case of the dual‐channel configuration, where both the working and reference/counter electrodes are placed deep within a channel, there is additional positive potential (with respect to ground) on both electrodes due to the separation voltage [14, 27].…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the separation voltage with a working electrode placed in an in‐channel configuration leads to a negative half‐wave potential shift under reverse polarity conditions using a single channel method . In the case of the dual‐channel configuration, where both the working and reference/counter electrodes are placed deep within a channel, there is additional positive potential (with respect to ground) on both electrodes due to the separation voltage [14, 27].…”
Section: Resultsmentioning
confidence: 99%
“…To decrease the analysis time and improve peak shape, a negative polarity was employed. DTAB was added to the run buffer to reverse the electroosmotic flow (EOF). , …”
Section: Resultsmentioning
confidence: 99%
“…Chip A (Figure A) was used to optimize the separation and detection conditions for nitrite. Isolation of the separation voltage from the EC detector was accomplished by employing an end-channel detection scheme. , Previous work in conventional CEEC with an end-column electrode alignment scheme using a negative polarity and reversed EOF has shown that the half-wave potential of an analyte is shifted to more negative values, and the extent of this shift is dependent upon the separation voltage . Therefore, the detection potential needs to be optimized for each particular separation voltage.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it seems reasonable to expect a further enhancement of the separation capacity of the ITP stage by using the electrolyte system providing larger differences in the effective mobilities of bromate and typical drinking water macroconstituents. Also an improvement in the detectability of bromate seems feasible and, for example, the use of amperometric or potentiometric detection can be very beneficial in this respect [59,60].…”
Section: Discussionmentioning
confidence: 99%